'A bigger living room required a bigger TV': Doing and negotiating necessity in well-to-do households. (November 2020) - Aro, Riikka
This article investigates how necessity is 'done' and 'negotiated' in Finnish well-to-do households' domestic practices and asks whether and how households are engaged in sustainable practices. The main research material consists of 14 in-depth interviews. In this study, necessities are viewed as something that householders perceive they 'cannot manage without' in their normal domestic daily life. At collective level, necessity is considered to construct 'expectation horizons': what is considered normal for people to have and to desire and how to live their lives normally within a certain socio-economic frame. With a novel theoretical approach, this article views necessity through three kinds of agentic capacities: distributed agency in the material world, socio-cultural surroundings and mental and bodily dispositions. This article contributes to the ongoing discussion on the problematics of rising living standards and household sustainability efforts. The findings show that in carrying out daily life, the leeway provided by higher income and education collides with the internalised ethos of 'not wasting' (habitus), lack of seeing real possibilities and often blurred views of responsibilities and power to pursue sustainability. Sustainability is seen as distant to daily life and as an inconvenience that requires familiarisation, time and/or money. It also lacks practical meaning. Instead, domestic necessity contributes to personal and family well-being and effortlessness and straightforwardness in daily life. This article provides three key conclusions. First, any vision or innovation for pursuing sustainability is inadequate if it does not carry meaning in everyday functionality. Second, it is important to critically account for the 'stickiness' (capacities for resisting change) of non-negotiable parts of domestic practices with embedded consumption of materials, water and electricity; third, based on the previous two, research and policy should take seriously the difficulty of thinking or seeing outside of the 'expectation horizons' that incorporate the co-evolving aspirations and conventions.